2015
DOI: 10.1159/000431094
|View full text |Cite
|
Sign up to set email alerts
|

Monomicrobial Necrotizing Fasciitis Caused by <b><i>Aeromonas</i></b> <b><i>hydrophila</i></b> and <b><i>Klebsiella pneumoniae</i></b>

Abstract: Objective: To compare specific characteristics and clinical outcomes of monomicrobial necrotizing fasciitis caused by Aeromonashydrophila and Klebsiella pneumoniae. Material and Methods: Cases of monomicrobial necrotizing fasciitis caused by A. hydrophila (n = 11) and K. pneumoniae (n = 7) over an 8-year period were retrospectively reviewed. Differences in mortality, patient characteristics, clinical presentations, and laboratory data were compared between the A. hydrophila and the K. pneumoniae groups. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…Another study conducted in Taiwan between 2008 and 2010 showed that the incidence of bacteremia by Aeromonas was 76 cases per one million individuals [153]. Those studies therefore show that the incidence of diseases caused by Aeromonas vary by geographical location and can be related to bad hygiene habits in undeveloped regions [3,5,[152][153][154][155][156][157][158].…”
Section: Aeromonas In Human Infectionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Another study conducted in Taiwan between 2008 and 2010 showed that the incidence of bacteremia by Aeromonas was 76 cases per one million individuals [153]. Those studies therefore show that the incidence of diseases caused by Aeromonas vary by geographical location and can be related to bad hygiene habits in undeveloped regions [3,5,[152][153][154][155][156][157][158].…”
Section: Aeromonas In Human Infectionsmentioning
confidence: 99%
“…Aeromonas infections often involve more than one type of bacteria in the same clinical sample, which is defined as a polymicrobial or mixed infection [3,5,152,[154][155][156]183]. Polymicrobial infections occur in 80% of cases of respiratory tract infections and cholangitis cases, and in 77% of cases of surgical site infections, followed by 60% of wound infections, and 30% of bacteremia [5,152,167,183].…”
Section: Aeromonas In Human Infectionsmentioning
confidence: 99%
See 2 more Smart Citations
“…and Aeromonas spp. have been regarded as the most important gram-negative bacteria causing NF since 2004 [8,9,[11][12][13][17][18][19][20][21][22], and Vibrio cholerae non-O1 keratitis [23]. Our team, "Vibrio NSSTIs Treatment and Research (VTR) Group," at CGMH-Chiayi consists of professional medical staff working in various departments, namely, emergency medicine, orthopedic surgery, infectious diseases, intensive care unit, and hyperbaric oxygen treatment center.…”
Section: Introductionmentioning
confidence: 99%